2020
DOI: 10.1093/jnen/nlaa055
|View full text |Cite
|
Sign up to set email alerts
|

CD33 and SIGLECL1 Immunoglobulin Superfamily Involved in Dementia

Abstract: Abstract Sialic acid-binding immunoglobulin-type lectins, which are predominantly expressed in immune cells, represent a family of immunomodulatory receptors with inhibitory and activating signals, in both healthy and disease states. Genetic factors are important in all forms of dementia, especially in early onset dementia. CD33 was recently recognized as a genetic risk factor for Alzheimer disease (AD). Here, we present a 2-generation family with 4 members, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Based on the evidence of the possible involvement in an unusual form of dementia of the SNP rs2455069-A>G in exon 2 of CD33 gene [ 29 ], leading to a change from arginine to glycine in position 69, we widened the analysis of this SNP to a cohort of AD patients from southern Italy. We found that the genotype frequency for the rs2455069 polymorphism in the control group was 11.1% ( n = 15) for the GG, 53.0% ( n = 77) for the AG, and 31.8% ( n = 43) for the AA genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the evidence of the possible involvement in an unusual form of dementia of the SNP rs2455069-A>G in exon 2 of CD33 gene [ 29 ], leading to a change from arginine to glycine in position 69, we widened the analysis of this SNP to a cohort of AD patients from southern Italy. We found that the genotype frequency for the rs2455069 polymorphism in the control group was 11.1% ( n = 15) for the GG, 53.0% ( n = 77) for the AG, and 31.8% ( n = 43) for the AA genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution melting analysis (HRM) was performed as previously described [ 29 ] on a LightCycler 480 Instrument II (Roche, Basel, Switzerland) and analyzed using LightCycler ® 480 Gene Scanning Software 1.5.1. High-resolution melting Mastermix (Roche) was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genes MARVELD2 and MGMT were also identified in the single CpG site analyses. The increased expression of gene SIGLECL1 , which is located in chr19: 51774377–51774667, has been found in patients with dementia (54). The three CpGs (i.e., cg14724749, cg14884932, cg15497724) are mapped to either the island or N shore area of gene SIGLECL1 , and their methylation levels were all negatively (although not statistically) associated with optimism level in the single CpG site analyses (data not shown).…”
Section: Discussionmentioning
confidence: 99%